A guide for the generation of repositories of clinical samples for research on Chagas disease. - Nieves Martínez-Peinado; Juan Carlos Gabaldón-Figueira; Roberto Rodrigues Ferreira; María Carmen Thomas; Manuel Carlos López; Tania Cremonini Araújo-Jorge; Belkisyolé Alarcón de Noya; Soledad Berón; Janine Ramsey; Irene Losada Galván; Alejandro Gabriel Schijman; Adriana González Martínez; et al. (Public Library of Science (PLoS), 2024)
Chagas disease, caused by the parasite Trypanosoma cruzi, affects over 6 million people, mainly in Latin America. Two different clinical phases, acute and chronic, are recognised. Currently, 2 anti-parasitic drugs are available to treat the disease (nifurtimox and benznidazole), but diagnostic methods require of a relatively complex infrastructure and trained personnel, limiting its widespread use in endemic areas, and the access of patients to treatment. New diagnostic methods, such as rapid tests (RDTs) to diagnose chronic Chagas disease, or loop-mediated isothermal amplification (LAMP), to detect acute infections, represent valuable alternatives, but the parasite's remarkable genetic diversity might make its implementation difficult. Furthermore, determining the efficacy of Chagas disease treatment is complicated, given the slow reversion of serological anti-T. cruzi antibody reactivity, which may even take decades to occur. New biomarkers to evaluate early therapeutic efficacy, as well as diagnostic tests able to detect the wide variety of circulating genotypes, are therefore, urgently required. To carry out studies that address these needs, high-quality and traceable samples from T. cruzi-infected individuals with different geographical backgrounds, along with associated clinical and epidemiological data, are necessary. This work describes the framework for the creation of such repositories, following standardised and uniform protocols, and considering the ethical, technical, and logistic aspects of the process. The manual can be adapted according to the resources of each laboratory, to guarantee that samples are obtained in a reproducible way, favouring the exchange of data among different work groups, and their generalizable evaluation and analysis. The main objective of this is to accelerate the development of new diagnostic methods and the identification of biomarkers for Chagas disease.